2007
DOI: 10.1029/2006ja012021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic activity linked generation of nighttime equatorial spread F irregularities

Abstract: Results derived from a statistical study of the generation of equatorial spread F (ESF) irregularities as a result of magnetic activity based on spaced receiver ionospheric scintillation data recorded at a dip equatorial station is reported here. For a study of this nature it is essential to establish whether the observed scintillations are caused by freshly generated irregularities or by irregularities generated earlier, which later drift onto the signal path. It has been observed in the past that the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…If we compare Q‐ and D‐days, we find that the postmidnight occurrence of F‐ESF is more likely on D‐days as compared to Q‐days. This tendency is in general agreement with the earlier studies (Abdu et al, ; Kakad et al, ; Li et al, ) and attributed to the westward to eastward reversal of ambient electric field around midnight due to DD electric fields (Fejer & Scherliess, ; C.‐M. Huang et al, ; Richmond et al, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…If we compare Q‐ and D‐days, we find that the postmidnight occurrence of F‐ESF is more likely on D‐days as compared to Q‐days. This tendency is in general agreement with the earlier studies (Abdu et al, ; Kakad et al, ; Li et al, ) and attributed to the westward to eastward reversal of ambient electric field around midnight due to DD electric fields (Fejer & Scherliess, ; C.‐M. Huang et al, ; Richmond et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Studies have demonstrated that on disturbed (D) days, a disturbance dynamo (DD) electric field (Blanc & Richmond, ), promptly penetrated (PP) electric field (Kikuchi et al, , ), or combination of DD and PP electric fields affects the dynamics of F‐region (Kakad et al, ; N. Maruyama et al, ). Apart from usual postsunset generation, fresh development of EPBs is often encountered in the postmidnight hours on the D‐days (Kakad et al, ). The seasonal and solar flux dependence of these magnetic activity linked F‐EPBs is not studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…C I is often found to be <0.5 in the initial phase of EPB development due to presence of perturbation electric fields associated with the R‐T instability but remains close to 1 in the later phase under magnetically quiet periods. Using this technique, Kakad et al [2007] have studied the fresh generation of irregularities around midnight hours and suppression of scintillations during pre‐midnight hours during magnetically active periods. From Tiwari et al [2006], one can notice that smaller the C I , higher the maximum height reached by the irregularity layer.…”
Section: Discussionmentioning
confidence: 99%
“…During geomagnetically active periods, plasma bubbles can be generated after midnight which are probably affected by electric perturbations associated with the magnetic activity [ Bhattacharyya et al , 2002; Kakad et al , 2007; Tulasi Ram et al , 2008]. Kakad et al [2007] studied local time when plasma bubbles were generated with ground‐based scintillation measurement. According to their study, plasma bubbles are mostly generated around midnight hours during disturbed days.…”
Section: Discussionmentioning
confidence: 99%